Publishing and Promotion in Economics: The Tyranny of the Top Five - James J. Heckman; Sidharth Moktan (Institute of Labor Economics (IZA), 2018)
This paper examines the relationship between placement of publications in Top Five (T5) journals and receipt of tenure in academic economics departments. Analyzing the job histories of tenure-track economists hired by the top 35 U.S. economics departments, we find that T5 publications have a powerful influence on tenure decisions and rates of transition to tenure. A survey of the perceptions of young economists supports the formal statistical analysis. Pursuit of T5 publications has become the obsession of the next generation of economists. However, the T5 screen is far from reliable. A substantial share of influential publications appear in non-T5 outlets. Reliance on the T5 to screen talent incentivizes careerism over creativity. The appendices for this paper are available here: https://hceconomics.uchicago.edu/file-upload/appendices-publishing-and-promotion-economics-tyranny-top-five
Keywords: A14; I23; J44; O31; 330; tenure and promotion practices; career concerns; economics publishing; citations